The antiferromagnetic structure of BaPrO3 - Goossens, D.J.; Robinson, R.A.; Telling, M.T.F. (Physica. B, Condensed matter, 2004)
In this study, we report the magnetic space group and moment direction in the canted antiferromagnetic system BaPrO3. While previous work had shown that perovskite-based BaPrO3, which is orthorhombic crystallographically, orders antiferromagnetically below 11.7K, and that it also exhibits weak ferromagnetism at the same temperatures, the exact magnetic symmetry and moment directions were previously undetermined. In this report, we show, by means of cold-neutron high-resolution powder diffraction, that the magnetic (Shubnikov) group is in fact Pb′n′m, and that the antiferromagnetism lies along the a-axis, with μx=0.37±0.03μB. This is qualitatively and quantitatively consistent with previous neutron diffraction results reporting the configurational symmetry of the antiferromagnetism. Our model explicitly allows for ferromagnetism, and necessarily implies that the ferromagnetism previously observed in bulk magnetisation measurements must lie along the z-axis (c direction). We discuss ways in which this prediction might be tested, even in the absence of single crystals of BaPrO3.